Identification of constitutive laws' parameters by means of experimental tests on AlSi-PE abradable coating. (June 2022) - Chevrier, B.; Vincent, J.; Faure, L.; Philippon, S.
Graphical abstract: Highlights: Study of the volume conservation and the strain field homogeneousness of an AlSi-PE specimen during a Split Hopkinson Bar Pressure test. Expression of experimental data by considering true stress and true strain values and adiabatic heating. Standard Johnson–Cook law taking into account a dependence between temperature and strain-rate sensitivity. Original and modified Johnson–Cook damage law introduction to experimental quasi-static tests that led to failure. Abstract: Abradable coatings are a part of dynamic seals used in aircraft engines to diminish inter-stage leakages by reducing rotor/stator clearances of the low and high-pressure compressors. However, interactions may occur during running between the rotating blades and the coating sprayed onto the casing. Due to the complexity of reproducing experimentally rotor/stator interactions, modeling approaches are used to optimize the choice of abradable coating, making constitutive laws necessary input data for rotor/stator interaction studies. Previous experimental researches were done to explore the dynamic and quasi-static compressive thermomechanical behavior of AlSi-PE abradable coating [1, 2]. Using results from these investigations and from a complementary experimental characterization coupled with a high speed camera, parameters of a standard Johnson–Cook constitutive law have been identified for the wide ranges of strain-rate and temperature explored. Although modeling data were in satisfactory agreement with the experimental results, an original constitutive law formulation has been proposed to better predict the thermomechanical behavior of AlSi-PE abradable material at high temperatures. As an introduction of damage into the modeling, a standard and modified Johnson–Cook damage law, describing a strain criterion from which failure theoretically begins, has been included and analyzed when modeling the coating's behavior by considering only quasi-static conditions.